Screening for attention deficit–hyperactivity disorder (ADHD) symptomatology in adult mental health clinics. (28th September 2017) - Adamis, D.; Graffeo, I.; Kumar, R.; Meagher, D.; O'Neill, D.; Mulligan, O.; Murthy, S.; O'Mahony, E.; McCarthy, G.; Gavin, B.; McNicholas, F.
Abstract : Objectives: This study estimates the symptomatology of attention deficit–hyperactivity disorder (ADHD) in adult mental health services (AMHS) outpatient clinics. Methods: All consecutive patients attending any of the outpatients' clinics in Sligo/Leitrim AMHS were invited to participate. Participants completed the Adult ADHD Self-Report Scale (ASRS) and the Wender Utah Rating Scale (WURS) self-report. Clinical notes were reviewed to identify those with a pre-existing ADHD diagnosis. Results: From 822 attending the clinics, 62 did not meet inclusion criteria, 97 declined to participate and 29 had incomplete data in either of the screening scales, leaving 634 (77%) eligible for full study analysis. Mean age was 40.38 (s.d. : 12.85), and 326 (51.4%) were females. In total, 215 (33.9%) screened positive on the WURS for childhood onset ADHD and 219 (34.5%) participants scored positive on the ASRS. Applying a more stringent criteria of scoring above cut-offs on both scales, suggested 131 (20.7%) screened positive on both. Only three (2.3%) had a prior clinical diagnosis. Conclusions: This preliminary study suggests the possibility of relatively higher rates of ADHD in a general AMHS than previously thought, however, given the possibility of overlapping symptoms with other major psychiatric disorders in adulthood and recall bias further research is needed before drawing firm conclusions.